El trabajo infantil y su influencia en el desarrollo integral de las niñas, niños y adolescentes que realizan actividad ocupacional informal en el Centro de Abasto “Gran Colombia” de la ciudad de Loja - González Rivera, Génesis Macarena (2018)
The present research work entitled CHILD LABOR AND ITS INFLUENCE ON THE INTEGRAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS WHO CARRY OUT INFORMAL OCCUPATIONAL ACTIVITY AT THE "GRAN COLOMBIA" ABASTO CENTER OF THE CITY OF LOJA; It was based on a study of the actors involved in the problem, where the main purpose was based on demonstrating the existence of child labor in children and adolescents who perform informal occupational activity, and thus verify how this method impacts in its integral development. Through the theoretical foundations that support the main categories of study, it was possible to diagnose each one of the indicators that visualize this social phenomenon, and to confront it through the appropriate methodology to answer the problem, for this purpose the use of the scientific method and its auxiliary as is the inductive, deductive, analytical and synthetic. The population determined for the investigation is represented mainly in six children and adolescents divided partially in their gender; and in their parents and / or corresponding mothers, who perform informal occupational activity. Consequently, the winners of the "Gran Colombia" supply center, who are an indispensable part of the object of study. And finally, institutional authorities, which include the Secretary of the Cantonal Council, three members of the Cantonal Board and the administrator of the "Gran Colombia" supply center. 5 The truthful results reflected the situation of child labor, allowing to determine the nature of the object of study, where the child working population could be identified, and therefore to know the causes and consequences generated by this problem, and then translate the results into graphs. figures and statistical tables, and finally analyze and interpret them in compliance with the proposed objectives, thus reaching conclusions and recommendations of the investigation.